The Common Mosquito (Culex pipiens) Does Not Seem to Be a Competent Vector for Hepatitis E Virus Genotype 3 - Frías, Mario; Casades-Martí, Laia; Risalde, María Á.; López-López, Pedro; Cuadrado-Matías, Raúl; Rivero-Juárez, Antonio; Rivero, Antonio; Ruiz-Fons, Francisco (Frontiers in Veterinary Science, 2022)
An experimental infection approach was used to estimate the competence of the common mosquito, Culex pipiens, for hepatitis E virus replication and transmission, using an isolate of hepatitis E virus genotype 3 of human origin in varying infectious doses. The experimental approach was carried out in biosafety level 2 conditions on three batches of 120 Cx. pipiens females, each using an artificial feeding system containing the virus in aliquots of fresh avian blood. Mosquitoes from each batch were collected 1, 7, 14, and 21 days post-infection (dpi) and dissected. The proboscis was subjected to forced excretion of saliva to estimate potential virus transmission. HEV RNA presence in abdomen, thorax, and saliva samples was analyzed by PCR at the selected post-infection times. HEV RNA was detected in the abdomens of Cx. pipiens females collected 1 dpi in the two experimentally-infected batches, but not in the saliva or thorax. None of the samples collected 7–21 dpi were positive. Our results show that Cx. pipiens is not a competent vector for HEV, at least for zoonotic genotype 3.